Humanizing Film Workers through Film Policies: Comparative Study of Indonesia and the Philippines Film Industries - Yubel, Novrel Esa; Hikmah, Nurul (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2026)
This article analyzes Indonesian and Philippine film policies and interprets their orientations toward protecting and improving the welfare of film workers. This article also aims to offer policy development to the Indonesian government based on lessons learned from the Eddie Garcia Law in the Philippines. This research enhances the application of the “Inspiration” and “Emulation” indicators within Policy Transfer theory as an analytical tool to identify potential for knowledge transfer and the evolution of more humanistic norms for safeguarding film workers in the national film industry. This article used a qualitative research approach, with a literature review as a data collection technique and NVivo 12 for data processing, analysis, and visualization. The findings indicated that the Eddie Garcia Law contains important and specific provisions that support the welfare and protection of film workers. In contrast, Indonesian film policy does not specifically address their welfare. This article offers an innovative policy in the format of a checklist model that the Indonesian government might utilize as a tool for pre-production film feasibility assessment, with evaluation criteria adapted from the analysis of the Eddie Garcia Law.